2016
DOI: 10.1039/c6cp04622c
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the chemistry of Mn-doped MgO for bulk and (100) surfaces

Abstract: We have investigated the energetic properties of Mn-doped MgO bulk and (100) surfaces using a QM/MM embedding computational method, calculating the formation energy for doped systems, as well as for surface defects, and the subsequent effect on chemical reactivity. Low-concentration Mn doping is endothermic for isovalent species in the bulk but exothermic for higher oxidation states under p-type conditions, and compensated by electrons going to the Fermi level rather than cation vacancies. The highest occupied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 74 publications
4
30
0
Order By: Relevance
“…An example application of this nature is CO 2 adsorption over the (100) surface of Mn-doped MgO, with and without neighboring anion vacancies. The results showed that the multivalent Mn caused chemical bonding between the support and the adsorbate that was not present for undoped-MgO, which complements experimental observations for mixed Fe-MnO/MgO catalysts as being reactive for the formation of light olefins from syngas…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…An example application of this nature is CO 2 adsorption over the (100) surface of Mn-doped MgO, with and without neighboring anion vacancies. The results showed that the multivalent Mn caused chemical bonding between the support and the adsorbate that was not present for undoped-MgO, which complements experimental observations for mixed Fe-MnO/MgO catalysts as being reactive for the formation of light olefins from syngas…”
Section: Introductionsupporting
confidence: 81%
“…The QM/MM cluster was centered on the atomic species of interest: the O-centered model contains 14 Mn and 19 O atoms (Figure ), whereas the Mn-centered model contains 14 O and 19 Mn atoms. Previous work has shown a model of this size is optimal as it ensures the QM region is large enough not to exhibit quantum confinement effects, which may occur due to the localized nature of the occupied states, while also not being excessively large so as to make calculations prohibitively expensive. ,, We also note here that stoichiometry is not a requirement for the QM region in the QM/MM embedded-cluster approach. After geometry optimization, the AFM­(II) electronic structure was preserved in both models, with Mulliken analysis showing an average spin density of 4.8 e on each Mn 2+ cation when using either XC functional, in agreement with experiment; however, the geometric structure is noted as being slightly distorted. For both the B3LYP and B97-3 O-centered models of pristine MnO, the mean bond distances in the QM region stay constant at 2.21 Å but in a range of 2.16–2.24 Å, with bond lengths longer in the center of the QM region.…”
Section: Bulkmentioning
confidence: 78%
“…This approach builds upon the earlier work of (Norgett, 1971), who modelled a vacancy in binary metal oxides using a set of Gaussian basis functions to describe the wave function, embedded within a lattice of polarisable ions represented by point charges. The boundary conditions allow one to access an absolute reference energy, from which ionisation energies can be calculated consistently (see Section 3.1), while two-dimensional (Berger et al, 2014;Berger et al, 2015;Downing et al, 2014a, b;Dutta et al, 2012;Goumans et al, 2008;Herschend et al, 2004;Keal et al, 2011;Logsdail et al, 2016;Sokol et al, 2004;Stefanovich and Truong, 1997) and one-dimensional (Buckeridge et al, 2013;Oliva et al, 2008) systems pose no significant problems to the technique.…”
Section: Modelling Point Defects With Hybrid Quantum Mechanical / Molmentioning
confidence: 99%
“…The development of hybrid quantum/molecular mechanical approaches has been beneficial for catalysis particularly when employing wide bandgap materials such as MgO; the high stability and low polarizability of these materials mean that it is relatively facile to introduce a small, focused QM region surrounded by an polarisable MM region with minimal geometric and electronic inconsistences around the interfacial region. 14 The reduced number of electrons that need be considered in the focused QM region allows for higher levels of theory than those which are accessible with periodic Scheme 1: Simplified reaction scheme for the production of methanol from glycerol.…”
Section: Introductionmentioning
confidence: 99%